Tocotrienol-rich Fraction Modulates Cardiac Metabolic Profile changes in Isoprenaline-Induced Myocardial Infarction rats - Khairul Anwar Zarkasi; Satirah Zainalabidin; Tan Jen Kit; Nur Haleeda Hakimi; Nur Zuliani Ramli; Zakiah Jubri (2020)
In myocardial infarction (MI), the occurrence of energy depletion, oxidative stress, and decreased amino acids metabolism alter tissue metabolites. Evidence has shown that tocotrienol-rich fraction (TRF) prevents myocardial injury in MI. However, the protective mechanism at the metabolite level is unknown. Male Sprague-Dawley rats were grouped into control, isoprenaline (ISO)-induced MI (MI), healthy rats receiving 200 mg/kg TRF (200TRF), and MI rats receiving 200 mg/kg TRF (200TRF+MI) groups. TRF was administered via oral gavage daily for 12 weeks followed by intraperitoneal ISO injection (85 mg/kg) for two consecutive days at a 24-hour interval to induce MI. High-performance liquid chromatography was performed to analyze serum α-tocopherol and tocotrienol concentration whereas ultrahigh-performance liquid chromatography-mass spectrometry was used for the untargeted metabolomic study. Serum α-tocopherol but not tocotrienol was increased in the 200TRF (p=0.121) and 200TRF+MI (p<0.05) following TRF supplementation. Multivariate analysis by Orthogonal Projections to Latent Structures Discriminant Analysis showed high predictability of the group comparison models for MI vs control and 200TRF+MI vs MI (cross-validation: Q2 >0.7, R2 Y>0.8, p<0.05). A total of 84 and 37 metabolites [when covariance of p≥|0.05| (magnitude) and p(corr)≥|0.5| (reliability)] were significantly different in the myocardial homogenates of MI vs control and 200TRF+MI vs MI, respectively. MI rats had reduced S-adenosylmethionine and L-cystathionine that might worsen MI by disturbing glutathione metabolism; decreased phosphoribosyl-pyrophosphate and purine salvage process that might impair DNA synthesis, and elevated glucose-6-phosphate suggesting enhanced anaerobic glycolysis possibly for rapid production of energy. Conversely, TRF supplementation reversed the impaired metabolic pathways caused by MI.